Photon attenuations of trichloride of gadolinium by Geant4 and XCom: a comparative study. Issue 1 (31st December 2023) - Saim, A.; Belkharroubi, F.; Maroc, F.Z.; Blaha, L.F.; Ameri, I.; Ameri, M.; Tebboune, A.; Belkaid, M.N.; Al-Douri, Y.
Abstract : The total mass attenuation coefficient of trichloride gadolinium has been investigated utilizing Geant4 compared with WinXCom simulation data at energies; 1–10 MeV. The simulated results are used to calculate the total cross section, atomic and electronic cross sections. The aim of this work is to characterize new materials and their interactions with radiation in order to be able for using in shielding or detection. The GdCl3 is applied for super–Kamiokande detector of neutrons. From our comparison study, it is found that the mass attenuation coefficient of GdCl3 with those of two detectors of X-ray (Si and CdTe) is very closed. Also, the total mass transfer attenuation coefficient increases as high energies increases at pairs effect production. From our comparison study, we can predict that GdCl3 can be a good detector of X-ray and concluded that this material has shown good interaction with electromagnetic radiations at high energies.